HISTOLOGI PENUAAN KULIT AKIBAT PHOTOAGING: ARTIKEL REVIEW - Vani, Ade Teti; Rosmaini, Rosmaini; Nadia Purnama Dewi; Yuliza Birman; Melya Susanti; Rinita Amelia (Nusantara Hasana Journal, 2025)
Photoaging is a complex skin aging process that results from prolonged exposure to ultraviolet (UV) light, leading to notable histological changes. This type of damage can affect both the epidermis and dermis layers of the skin. The purpose of this review article is to highlight and summarize the recent findings from the past five years concerning the histology associated with photoaging and the molecular mechanisms that contribute to this skin damage. The methodology employed involved a thorough literature review of articles published between 2020 and 2025. Journals were identified using targeted keywords, including "photoaging," "skin aging," "histology," and "actinic elastosis." The findings from this search are presented in a narrative format. The study found that UV exposure causes photoaging of the skin with damage to the epidermis and dermis. Photoaging causes structural and functional changes in the skin and causes gene mutations leading to skin carcinogenesis.